The Effect of Self Efficacy, Working Conditions and Employee Retention on Plantation Employee Performance Through Work Discipline at PT Socfindo Labuhanbatu Utara - Putri Latifah Anum; Prihatin Lumbanraja; Yeni Absah (Indonesian Journal Publisher, 2025)
The performance of plantation employees has become an important issue in today’s modern and digital era, considering the declining interest of younger generations in working in the plantation sector, particularly in tapping positions. This study aims to analyze the influence of self-efficacy, job conditions, and employee retention on the performance of plantation employees through work discipline at PT Socfindo Labuhanbatu Utara. This research is an associative quantitative study with a population consisting of all plantation employees at PT Socfindo Aek Pamingke, totaling 979 employees. The sample used consists of 284 employees selected through non-probability sampling using an incidental sampling approach, with the criterion that employees must have worked for at least 10 years. Data analysis was conducted using structural equation modeling (SEM) with the assistance of Smart PLS software. The results show that self-efficacy has a direct positive and significant effect on employee performance, but a negative and insignificant effect on work discipline. Job conditions have a significant negative effect on both employee performance and work discipline. Employee retention has a significant positive effect on both employee performance and work discipline. Moreover, work discipline itself has a significant positive effect on employee performance. Indirectly, self-efficacy and job conditions do not have a significant effect on performance through work discipline, whereas employee retention has a significant.